2013
DOI: 10.1093/hmg/ddt383
|View full text |Cite
|
Sign up to set email alerts
|

Armet/Manf and Creld2 are components of a specialized ER stress response provoked by inappropriate formation of disulphide bonds: implications for genetic skeletal diseases

Abstract: Mutant matrilin-3 (V194D) forms non-native disulphide bonded aggregates in the rER of chondrocytes from cell and mouse models of multiple epiphyseal dysplasia (MED). Intracellular retention of mutant matrilin-3 causes endoplasmic reticulum (ER) stress and induces an unfolded protein response (UPR) including the upregulation of two genes recently implicated in ER stress: Armet and Creld2. Nothing is known about the role of Armet and Creld2 in human genetic diseases. In this study, we used a variety of cell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 59 publications
7
87
0
Order By: Relevance
“…CHOP plays an inducer role in cell death. The expression of CHOP is also strongly enhanced in ER-induced apoptosis in a variety of cell types (Gotoh et al, 2002;Tsukano et al, 2010;Hartley et al, 2013). Therefore, the increase of mRNA and protein expression levels of GRP78 and CHOP in our study supported the involvement of ER apoptotic pathway in CS 2 induced Sertoli cell apoptosis.…”
Section: Discussionsupporting
confidence: 79%
“…CHOP plays an inducer role in cell death. The expression of CHOP is also strongly enhanced in ER-induced apoptosis in a variety of cell types (Gotoh et al, 2002;Tsukano et al, 2010;Hartley et al, 2013). Therefore, the increase of mRNA and protein expression levels of GRP78 and CHOP in our study supported the involvement of ER apoptotic pathway in CS 2 induced Sertoli cell apoptosis.…”
Section: Discussionsupporting
confidence: 79%
“…In the last few years, it has been reported that the expression of CRELD2 and MANF are elevated in several physiological conditions, which are not restricted to the central nervous system. 23,[37][38][39] Therefore, further characterization of MANF and CRELD2 inside and outside cells under pathophysiological conditions may give new insights into the onset and progression of ER stress-related diseases. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , MANF expression is upregulated in cell lines derived from bone tissue (U2OS), kidneys (HEK293), neuroblastoma (SH-SY5Y) and embryo fibroblasts (NIH 3T3) in response to ER stress triggered by tunicamycin (TM), thapsigargin (TG), and lactatystin 26, 33 . In vivo , MANF expression is induced in chondrocytes following ER retention of the mutant cartilage extracellular matrix protein in mouse knock-in models of chondrodysplasia caused by matrilin-3 or type × collagen mutations 34 , in pancreatic ÎČ cells following misfolding of mutant proinsulin in Akita mouse model carrying an insulin C96Y mutation 26 , and in synoviocytes following inflammation mediated-ER stress in a rabbit antigen-induced arthritis model 29 . MANF expression is also increased in response to ischemia-induced ER stress both in vitro and in vivo 32, 33, 35–37 .…”
Section: Manf Expression and Upregulation Upon Er Stressmentioning
confidence: 99%